DEIKSIS DALAM BAHASA USING DI KABUPATEN BANYUWANGI - Syuhadak, Syuhadak; Wibisono, Bambang; Sariono, Agus (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2017)
Deixis is one of the lingual phenomenon which have the universal function as one of the center of something. This article is aimed to describe the using of expresion in the deixis of Banyuwangi, Using languange. The descriptive method is using to describe the phenomenon. The data were callected participation observation, interview, and introspekt reflektive. The data were analysed by teknik pilah unsur penentu and hubung banding technical. The result from this discusion is the using of promina persona in Osing language is influenced by the age, and heredity between the participants factors. Ekspression places on Using language will be deixis if used based on speakers prespektiv. Time ekspression have gain if the speaker as a deixis core when speech produses. That become a speech as time core, so time place by events that before, on, or after speech. Social deixis in Using language use on language greating be related on nick name, family, tittle, office, rank, name, and pronouns. Demontrativ locativ discourse deixis used to related of part discourse referred with the places. By referred on part before speech and after speech